Energetic Ion Composition as a Means of Investigating the Physical Origins of Alpha Particle Heavy Magnetic Switchbacks - Emily McDougall; Bala Poduval (The Astrophysical Journal)
Magnetic switchbacks are of continuing interest to the scientific community because the phenomenon has not been completely understood. Although most of the research into them in the Parker Solar Probe era has largely focused on creating a theoretical framework for causing the field reversal through magnetic interchange reconnection, reconnecting streams of plasma in the solar wind, or shear driven turbulence, it remains unclear as to what extent these models may or may not represent the underlying physical reality of magnetic switchbacks. In this paper, we present the results of our study on the energetic ion composition of magnetic switchback events using statistical methods with the aim of obtaining new insights into the underlying physics. In doing so, we find evidence that switchbacks containing suprathermal alpha flux display traits that are indicative of the Zank model of a magnetic “kink” propagating as a fast magnetosonic wave. These switchbacks also correlated with increased solar activity such as coronal mass ejections, high-speed streams, and solar flares. At the same time, switchbacks not meeting this criteria appear to occur at rates that are unaffected by increasing solar activity, which implies the existence of multiple populations of switchbacks with differing physical mechanisms behind them.